Cultural Routes of the Council of Europe: New Paradigms for the Territorial Project and Landscape - Berti, Eleonora (Almatourism - Journal of Tourism, Culture and Territorial Development, 2013)
The article aims at offering a methodological contribution to the study and project of cultural routes. The cultural routes are analysed considering their nature of complex territorial systems. The potential which cultural routes may develop, if considered as cultural complex and inclusive goods, is the understanding of the interactions with the landscape at the change of socio-economic and cultural contexts crossed. In this sense, cultural routes are tools of development for a landscape project based on the endogenous resources of the territories.